PENYULUHAN MANAJEMEN HIPERTENSI PADA DEWASA DAN LANSIA DI DESA SERUT SEBAGAI UPAYA PENINGKATAN PENGETAHUAN MANAJEMEN HIPERTENSI DI LINGKUNGAN MASYARAKAT DESA - Sri Wahyuni Adriani; Mochammad Foedhail; Muhammad Kandar; Nurdiyah Purnamasari (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2024)
Hypertension is a serious medical condition and can increase the risk of heart, brain, kidney and otherdiseases. Counseling on hypertension management for adults and the elderly in Serut village as an effort to increase knowledge of hypertension management in the village community. Based on the survey results, there were 223 people with a frequency of 63% who regularly went to Posbindu and 40 elderly people suffered from hypertension. The problem of concern at Posbindu is related to the elderly's lack of knowledge regarding hypertension and efforts to prevent it. The aim is to increase knowledge of hypertension in village communities. The method used in implementing community service activities is in the form of counseling. The results concluded that there was an increase in residents' knowledge about hypertension in Serut village after education regarding hypertension was in the sufficient (53,8%).criteria.